Feasibility Study of a Novel Experimental Induction Protocol Combining B43-PAP (Anti-CD19) Immunotoxin With Standard Induction Chemotherapy in Children and Adolescents With Relapsed B-Lineage ALL: A Report From the Children's Oncology Group. Issue 7 (September 2015) - Meany, Holly J.; Seibel, Nita L.; Krailo, Mark; Villaluna, Doojduen; Chen, Zhengjia; Gaynon, Paul; Neglia, Joseph P.; Park, Julie R.; Hutchinson, Raymond; Sato, Judith K.; Wells, Robert J.; Woods, William G.; et al.
Abstract : Background: B43-pokeweed antiviral protein (B43-PAP) is a high-affinity anti-CD19 immunotoxin that is capable of causing apoptotic death in B-lineage leukemic cells with a drug-resistant phenotype. B43-PAP exhibited in vivo antileukemic activity in preclinical studies as well as on a single-agent phase I clinical trial. This pediatric phase I/II study evaluated the toxicity profile and efficacy of B43-PAP immunotoxin in combination with standard induction chemotherapy in children and adolescents with relapsed CD19-positive B-lineage acute lymphoblastic leukemia (B-ALL). Pharmacokinetic profile and immunogenicity of B43-PAP were assessed. Experimental Design: B43-PAP in combination with standard 3 and 4-drug induction chemotherapy was administered on days 9–13 and 21–25 of a 28-day treatment course with vincristine, prednisone, L-asparaginase, daunomycin, and intrathecal methotrexate. Thirty patients with relapsed B-ALL were enrolled on study CCG-0957. Results: Grade III/IV nonhematologic dose-limiting toxicities were encountered in 4 patients evaluable for toxicity and included myalgias, motor dysfunction, pulmonary toxicity, and elevated liver transaminase. Dose-limiting toxicities occurred only with the 4-drug regimen. Fourteen patients achieved a complete remission at the end of induction among the 20 patients evaluable for response. Conclusions: B43-PAP in combination with standard induction chemotherapy can be safely administered and exhibits clinical antileukemic activity against relapsed B-ALL. Abstract : Supplemental Digital Content is available in the text.